2024
DOI: 10.7150/thno.92463
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of extracellular vesicles in diabetic retinopathy

Junyan Zhu,
Jin Huang,
Yaoxiang Sun
et al.

Abstract: Diabetic retinopathy (DR), a complex complication of diabetes mellitus (DM), is a leading cause of adult blindness. Hyperglycemia triggers DR, resulting in microvascular damage, glial apoptosis, and neuronal degeneration. Inflammation and oxidative stress play crucial roles during this process. Current clinical treatments for DR primarily target the advanced retinal disorder but offer limited benefits with inevitable side effects. Extracellular vesicles (EVs) exhibit unique morphological features, contents, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 132 publications
0
2
0
Order By: Relevance
“…A survey by the International Diabetes Federation indicated that in 2021, approximately 537 million individuals aged 20–79 years were diagnosed with DM. Diabetic retinopathy (DR) is a severe complication of DM, and persistent hyperglycemia and hypertension can lead to retinal dysfunction, thus ultimately resulting in significant visual impairment and even blindness [ 1 ]. Factors such as hyperglycemia, hypertension, dyslipidemia, and duration of DM are associated with increased risks of DR [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A survey by the International Diabetes Federation indicated that in 2021, approximately 537 million individuals aged 20–79 years were diagnosed with DM. Diabetic retinopathy (DR) is a severe complication of DM, and persistent hyperglycemia and hypertension can lead to retinal dysfunction, thus ultimately resulting in significant visual impairment and even blindness [ 1 ]. Factors such as hyperglycemia, hypertension, dyslipidemia, and duration of DM are associated with increased risks of DR [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive understanding of EV-mediated disease mechanisms requires exploration of their entire cargo. Some interesting reviews about non-miRNA content in EVs on AMD and DR pathological process have already been published [11,12]. This review aims to give an overview also of some non-miRNA content, but specially to provide a more in-depth comprehension of the role of miRNA-containing EVs in the pathogenesis of retinal degenerative diseases.…”
Section: Introductionmentioning
confidence: 99%